The effect of rehabilitation sessions using specific flexibility and muscle strengthening exercises in relieving pain and improving leg muscle tone among physical education students - Qadir, Asst.L.Briar Osman (Sulaimani Journal for Humanities, 2026)
The research aims to prepare special rehabilitation exercises to improve muscle strength and lengthening to relieve pain for students with muscle strain at the College of Physical Education, and to identify the effect of special rehabilitation exercises in improving muscle strength and lengthening to relieve pain for students with muscle strain at the College of Physical Education. The researcher used the experimental method with a single group design with pre- and post-tests. The research population was defined as students with muscle strain at the College of Physical Education and Sports Sciences at the University of Sulaimani for the academic year (2024-2025), totaling (19) students. The research sample was limited to (12) students, after excluding those who were absent from the exercises, which numbered (3) students, and the pilot sample numbered (4) students. The sample size represented 63.15% of the population. The researcher used the following tests: the long seated trunk flexion test, the half-squat jump test, and the standing vertical jump test (Sargent's test). Following a pilot study and the development of the training sessions, which lasted eight weeks, the researcher conducted a program of 24 training sessions, with three exercises per week. Each training session progressed from least to most challenging, ranging from 15 to 30 minutes in duration. A pre-test, exercise application, and post-test were administered, and the researcher used an electronic statistical package to analyze the data. The researcher concluded that leg muscle lengthening and strength play a role in alleviating leg muscle pain. The researcher also concluded that the developed program improves muscle lengthening, flexibility, and strength. The researcher recommends using these leg muscle lengthening training exercises.